STIMULATED BRILLOUIN SCATTERING IN WAVEGUIDES - Ramadhan, Khaikal
Stimulated Brillouin Scattering (SBS) is a nonlinear optical phenomenon where high intensity pump optical waves produce acoustic waves through electrostriction process. This acoustic wave interacts with the pump wave to produce Stokes waves which of a longer wavelength which in turn provides feedback that increases the energy of the acoustic wave. The interaction between these increasing optical and acoustic waves produces scattered light that grows exponentially with a sharp spectrum. The characteristics of this SBS event are expressed by the Brillouin gain parameter which is basically obtained from the overlap integral of the optical and acoustic modes. Previous research has reported Brillouin gain calculations based on the Optical Force (OF) formulation, where the Brillouin gain is not only influenced by the classical paradigm of intrinsic material nonlinear effects in the form of electrostriction but also due to radiation pressure. In this thesis, the Acoustic Wave Perturbation (AP) formulation is applied in analyzing the optical and mechanical response of waveguides, where in calculating the scattering process the effects of Photoelasticity (PE) and Moving boundary (MB) are taken. This AP formulation avoids the uncertainties associated with the optical force contribution to the waveguide. To validate this AP formulation, the Brillouin gain of various waveguide structures, namely unsuspended silicon nanowaveguide, lithium niobate nanowaveguide (LiNBO3) on sapphire (Al2O3) substrate and arsenic trisulfide (As2S3) waveguide buried in silicon dioxide (SiO2), have been calculated. The Brillouin gain obtained from this AP formulation are the same as the values reported using different calculation methods and experimental observation results.